Outofshapeworthlessloser : a memoir of figure skating, f*cking up, and figuring it out - Gold, Gracie, 1995- (Crown, 2024)
"In this explosive tell-all memoir, an Olympic figure skater reveals her battle to survive mental illness, eating disorders, and the self-destructive voice inside that she calls "outofshapeworthlessloser." When Gracie Gold stepped onto center stage (or ice, rather) as America's sweetheart at the 2014 Sochi Olympics, she instantly became the face of America's most beloved winter sport. Beautiful, blonde, Midwestern, and media-trained, she was suddenly being written up everywhere from The New Yorker to Teen Vogue to People and baking cookies with Taylor Swift. But little did the public know what Gold was facing when the cameras were off. In 2017, she entered treatment for what was publicly announced as an eating disorder and anxiety treatment but was, in reality, suicidal ideation. While Gold's public star was rising, her private life was falling apart: Cracks within her family were widening, her bulimia was getting worse, and she became a survivor of sexual assault. The pressure of training for years with demanding coaches and growing up in a household that accepted nothing less than gold had finally taken its toll. Now Gold reveals the exclusive and harrowing story of her struggles in and out of the pressure-packed world of elite figure skating: the battles with her family, her coaches, the powers-that-be at her federation, and her deteriorating mental health. Told with unflinching honesty and stirring defiance, Outofshapeworthlessloser is not only a forceful reckoning from a world-class athlete but also an intimate account of surviving as a young woman in a society that rewards appearances more than anything and demands perfection at all costs"--